Gender Studies : Language and power in politics : the case of a femal leader in Algeria - AOUMEUR, Hayat (University of Mostaganem, 2010)
This dissertation is concerned with some applications of Critical Discourse Analysis in the study of the connections between discourse, gender and power. It is an attempt to investigate the roles that discourse play in creating, maintaining and challenging gender ideologies. The focus in this study is on women working in the domain of politics; their struggle to create new identities for themselves and their ability to cause novelty in terms of discourse and power relations. At this level the critical analysts’ aim is to reveal females’ attempts to resist existing gender ideologies and to exercise power discursively. Our aim in this dissertation is to illustrate such revelations through the investigation of the social and political contexts under which the Algerian political leader ‘Louisa Hanoune’ exercises power and through a critical analysis of her rhetorical style . Analysis of Hanoune’s discourse is conducted on both written (Interview, open letter) and spoken texts (TV interview, speeches, comments). It consists mainly of revealing those features of the text which express authority and toughness. My hope is that this study will contribute to provide some suitable answers to some enquiries related to issues of discourse, gender and power and add insight into this area of research.